Lineage negative (lin-) cell isolation, differentiation and characterization from umbilical cord blood/ Zulinda Ayu Zulkipli - Zulkipli, Zulinda Ayu (2007)
Among the well-established and mostly studied adult stem cells, umbilical cord blood-derived lineage negative (lin") cells were chosen to be studied. The stem cell has been regarded to have many potential applications due to its ability for selfrenewal and differentiation. Studies presented here showed that there is still uncertainty on the benefits of using positive markers such as CD34 in isolating the most primitive cells in Umbilical Cord Blood (UCB). By using selective markers, isolation and characterization of lineage negative (lin") cells were conducted. A novel negative selection protocol was designed to isolate the lineage negative cells of UCB from 50 mothers with normal full-term deliveries. The UCB samples were lysed using ammonium chloride lyses buffer and then stained with cocktails of monoclonal antibodies. The cells sorting of CD34"lin" were conduct by fluorescenceactivated cell sorter (FACS). Clonal culture of (FACS) CD34"lin" UCB cells revealed proliferation capacity in semi-solid methycellulose media by forming CFUGM and CFU-E. Currently, the isolated cells were unable to differentiate as true stem cells or very early progenitor cells. However, the study has proved that the isolated lin- UCB cells can be differentiated to B-lymphoid lineage when induced with specific cytokines. B-lymphoid cells were still considered blood cells; the true status of the lin" cells isolated from UCB is still unclear.